Indirect Speech Act Analysis in the Wonder Movie Script by R.J Palacio: Pragmatics Study - Eirene Pingkan Permata Giroth; Sasmi Farida (Budapest International Research and Critics University, 2022)
The purposes of this research are to find out the kinds of indirect speech act and to identify the meaning of illocutionary acts in the Wonder Movie produced by R.J Palacio. The method used in this study was descriptive analysis meaning that the researcher analyze by using context of the situation to find out what is the meaning of the speakers. The data source is taken from official movie script. The results of this research found that there are five types of indirect speech. They are 45% assertive, 30% directives, 15 % commissive 5 % expressive and the last 5% of declaration. From the analyze data, it can be concluded the most dominant types of Illocutionary act in that movie is assertive. However the meaning of this research found is literal meaning.